Mapping the effectiveness of nature‐based solutions for climate change adaptation. (9th September 2020) - Chausson, Alexandre; Turner, Beth; Seddon, Dan; Chabaneix, Nicole; Girardin, Cécile A. J.; Kapos, Valerie; Key, Isabel; Roe, Dilys; Smith, Alison; Woroniecki, Stephen; Seddon, Nathalie
Abstract: Nature‐based solutions (NbS) to climate change currently have considerable political traction. However, national intentions to deploy NbS have yet to be fully translated into evidence‐based targets and action on the ground. To enable NbS policy and practice to be better informed by science, we produced the first global systematic map of evidence on the effectiveness of nature‐based interventions for addressing the impacts of climate change and hydrometeorological hazards on people. Most of the interventions in natural or semi‐natural ecosystems were reported to have ameliorated adverse climate impacts. Conversely, interventions involving created ecosystems (e.g., afforestation) were associated with trade‐offs; such studies primarily reported reduced soil erosion or increased vegetation cover but lower water availability, although this evidence was geographically restricted. Overall, studies reported more synergies than trade‐offs between reduced climate impacts and broader ecological, social, and climate change mitigation outcomes. In addition, nature‐based interventions were most often shown to be as effective or more so than alternative interventions for addressing climate impacts. However, there were substantial gaps in the evidence base. Notably, there were few studies of the cost‐effectiveness of interventions compared to alternatives and few integrated assessments considering broader social and ecological outcomes. There was also a bias in evidence toward the Global North, despite communities in the Global South being generally more vulnerable to climate impacts. To build resilience to climate change worldwide, it is imperative that we protect and harness the benefits that nature can provide, which can only be done effectively if informed by a strengthened evidence base. Abstract : We present the first global systematic map of the effectiveness of nature‐based solutions (NbS) for addressing the impacts of climate change and hydrometeorological hazards on people. We found that most studies on NbS interventions in natural or semi‐natural ecosystems reported reduced climate impacts and that, overall, more synergies than trade‐offs were reported between addressing climate impacts and broader ecological, social and climate change mitigation outcomes. However, to strengthen the evidence base and support the upscaling of NbS, future studies should compare the cost‐effectiveness of NbS with engineered alternatives and consider social and ecological outcomes. More NbS research is also needed in the Global South.